2022
DOI: 10.1111/1742-6723.13925
|View full text |Cite
|
Sign up to set email alerts
|

Overdose and take‐home naloxone in emergency settings: A pilot study examining feasibility of delivering brief interventions addressing overdose prevention with ‘take‐home naloxone’ in emergency departments

Abstract: Objective Although most unintentional opioid deaths in Australia are attributed to pharmaceutical opioids, take‐home naloxone (THN) programmes have to date predominantly targeted people using illicit opioids in drug treatment and harm reduction settings. We sought to examine the feasibility of delivering THN brief interventions (THN‐BIs) with intranasal naloxone in EDs. Methods This pilot feasibility study was conducted across three major metropolitan EDs in Sydney and Melbourne. ED staff were surveyed about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Previous research findings, including those from the SuperMIX cohort [ 21 ], indicate frequent use of health services among people who inject drugs [ 22 ]. Recent self‐reported ambulance and/or emergency department utilization was associated with mortality risk in our study, which accentuates the need to scale up interventions involving these emergency services that aim to reduce future mortality events—such as making take‐home naloxone (THN) available from ambulance services, similar to recent efforts to make THN available through emergency departments [ 23 ], potentially with referrals to community THN providers for follow‐up. Research among broader populations of frequent ambulance attendees [ 24 ] or people who inject drugs who use emergency departments [ 21 ] indicates that reasons for calling emergency services for non‐urgent issues are complex and often misunderstood, and impacted by socio‐economic deprivation and lower income [ 28 ].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Previous research findings, including those from the SuperMIX cohort [ 21 ], indicate frequent use of health services among people who inject drugs [ 22 ]. Recent self‐reported ambulance and/or emergency department utilization was associated with mortality risk in our study, which accentuates the need to scale up interventions involving these emergency services that aim to reduce future mortality events—such as making take‐home naloxone (THN) available from ambulance services, similar to recent efforts to make THN available through emergency departments [ 23 ], potentially with referrals to community THN providers for follow‐up. Research among broader populations of frequent ambulance attendees [ 24 ] or people who inject drugs who use emergency departments [ 21 ] indicates that reasons for calling emergency services for non‐urgent issues are complex and often misunderstood, and impacted by socio‐economic deprivation and lower income [ 28 ].…”
Section: Discussionmentioning
confidence: 69%
“…Many studies that investigate mortality in broader populations at risk of opioid overdose, such as opioid‐dependent people and those receiving opioid treatment, link administrative databases of specialist drug treatment [ 11 , 12 , 13 , 14 , 15 ], health [ 10 , 16 , 17 , 18 , 19 , 20 , 21 ] or prison data [ 22 , 23 , 24 ] with mortality records. In these studies, injecting drug use is identified as a key risk factor, as are related issues such as HIV status [ 25 , 26 ], with opioid agonist treatment (OAT) typically protective [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…US guidelines for ED OUD management have highlighted the importance of naloxone prescribing for those with OUD [16]. Adoption of ED-based naloxone distribution is less common outside North America, although there have been promising pilot programs [37][38][39]. Our findings suggest that while efforts to boost prescribing of naloxone are important, these efforts will be most successful when paired with effective patient education and communication.…”
Section: Discussionmentioning
confidence: 82%
“…Sokol et al reported provider attitudes showed increasing understanding towards opioid users, and a desire to feel that they are making a difference to patients’ lives [ 33 ]. Hawk et al (2022) reported improving attitudes amongst ED staff towards opioid overdose survivors and a survey of staff in Canada and Australia showed around 9/10 of staff supported provision of THN in the ED [ 15 , 18 ])…”
Section: Discussionmentioning
confidence: 99%